Efek Financial Literacy dan Financial Management Behavior terhadap Financial Well-Being melalui Financial Self-Efficacy - Mardliyah, Dewi; Supriyanto, Agus (Jurnal Ekonomi dan Bisnis Islam, 2025)
Abstract This study investigates the role of financial literacy, financial management behaviour, and financial self-efficacy in shaping the financial well-being of Muslim Generation Z in Kudus Regency. In this research, financial self-efficacy is examined as a mediating construct. The study employs a quantitative design supported by a survey approach, involving 200 purposively selected respondents. The collected data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique through SmartPLS 4. The results indicate that financial literacy and financial management behaviour enhance both financial self-efficacy and financial well-being. Financial self-efficacy is also found to mediate part of the relationship between these variables and financial well-being. These findings stress the need to develop stronger financial practices and decision-making confidence among Muslim Gen Z. The study further recommends incorporating practical financial literacy into educational settings and suggests that future research broaden respondent diversity and integrate technological and socio-cultural perspectives to deepen insights into youth financial well-being. Keywords: Financial Literacy; Financial Management Behaviour; Financial Self-Efficacy; Financial Well-Being; Muslim Generation Z. Abstrak Penelitian ini menelusuri peran literasi keuangan, perilaku pengelolaan keuangan, dan efikasi diri keuangan dalam membentuk kesejahteraan keuangan Generasi Z Muslim di Kabupaten Kudus, dengan efikasi diri keuangan diposisikan sebagai variabel mediasi. Studi ini menggunakan pendekatan kuantitatif melalui survei yang melibatkan 200 responden terpilih secara purposive. Data yang diperoleh kemudian dianalisis menggunakan metode Structural Equation Modeling–Partial Least Squares (SEM-PLS) melalui aplikasi SmartPLS 4. Temuan penelitian mengungkap bahwa literasi keuangan dan perilaku pengelolaan keuangan memberikan kontribusi positif terhadap efikasi diri keuangan dan kesejahteraan keuangan. Selain itu, efikasi diri keuangan berperan sebagai mediator parsial dalam hubungan antara variabel-variabel tersebut. Hasil ini menegaskan perlunya penguatan praktik keuangan dan kemampuan membuat keputusan finansial di kalangan Generasi Z Muslim. Penelitian ini juga merekomendasikan pengintegrasian literasi keuangan praktis pada ranah pendidikan serta menyarankan penelitian lanjutan dengan sampel lebih beragam dan mempertimbangkan aspek teknologi maupun budaya untuk memperkaya pemahaman mengenai kesejahteraan keuangan generasi muda. Kata Kunci: Literasi Keuangan; Perilaku Pengelolaan Keuangan; Efikasi Diri Keuangan; Kesejahteraan Keuangan; Generasi Z Muslim.